A piezoresistive dual-tip stiffness tactile sensor for mango ripeness assessment. Issue 1 (31st December 2022) - Christopher, Chiebuka T.; Fath Elbab, Ahmed M. R.; Osueke, Christian O.; Ikua, Bernard W.; Sila, Daniel N.; Fouly, Ahmed
Abstract: Fruit ripeness detection (FRD) has been a very important research area. FRD has focused more on colour segmentation, image processing, odor of fruits and its size. However, fruit stiffness can be an evidence of its ripening. Developing a sensor that focuses on the stiffness of fruit becomes very important. This work presents an approach of mango ripeness detection based on its stiffness using a tactile sensor. A resistance change-based micro tactile sensor is designed for FRD in which it utilizes two cantilevers with different stiffness to estimate mangoes ripeness levels based on their stiffness. The tactile sensor parameters were analyzed and selected to ensure high sensitivity and linearity of the sensor output (Force ratio). The sensor was developed and experimentally tested with five test pieces of known stiffness for proof-of-concept. A finite element analysis was carried out to test the sensor with the same stiffness values of test pieces to compare the results with the analytical results. The error between the analytical and experimental results of the test pieces did not exceed 7%, while the error between the analytical and simulation results of the stiffness of the test pieces did not exceed 2.7%. Finally, the sensor was tested with five mangoes at different ripeness levels, and the sensor clearly differentiated among the mangoes and obtained stiffness values of 1792.95 N/m, 1395.70 N/m, 1078.86 N/m, 317.15 N/m and 67.81 N/m from the stiffest to the softest mango (Mango A—Mango E), respectively. This tactile sensor can be used in fruit sorting industries to complement the existing fruit sorting approaches.